Acute Toxicity of 6PPD‐Quinone to Early Life Stage Juvenile Chinook (Oncorhynchus tshawytscha) and Coho (Oncorhynchus kisutch) Salmon - Lo, Bonnie P.; Marlatt, Vicki L.; Liao, Xiangjun; Reger, Sofya; Gallilee, Carys; Ross, Andrew R.S.; Brown, Tanya M. (Environmental toxicology and chemistry, 2023)
The breakdown product of the rubber tire antioxidant N‐(1,3‐dimethylbutyl)‐N'‐phenyl‐p‐phenylenediamine‐quinone (6PPD)‐6‐PPD‐quinone has been strongly implicated in toxic injury and death in coho salmon (Oncorhynchus kisutch) in urban waterways. Whereas recent studies have reported a wide range of sensitivity to 6PPD‐quinone in several fish species, little is known about the risks to Chinook salmon (Oncorhynchus tshawytscha), the primary prey of endangered Southern Resident killer whales (Orcinus orca) and the subject of much concern. Chinook face numerous conservation threats in Canada and the United States, with many populations assessed as either endangered or threatened. We evaluated the acute toxicity of 6PPD‐quinone to newly feeding (~3 weeks post swim‐up) juvenile Chinook and coho. Juvenile Chinook and coho were exposed for 24 h under static conditions to five concentrations of 6PPD‐quinone. Juvenile coho were 3 orders of magnitude more sensitive to 6PPD‐quinone compared with juvenile Chinook, with 24‐h median lethal concentration (LC50) estimates of 41.0 and more than 67 307 ng/L, respectively. The coho LC50 was 2.3‐fold lower than what was previously reported for 1+‐year‐old coho (95 ng/L), highlighting the value of evaluating age‐related differences in sensitivity to this toxic tire‐related chemical. Both fish species exhibited typical 6PPD‐quinone symptomology (gasping, increased ventilation, loss of equilibrium, erratic swimming), with fish that were symptomatic generally exhibiting mortality. The LC50 values derived from our study for coho are below concentrations that have been measured in salmon‐bearing waterways, suggesting the potential for population‐level consequences in urban waters. The higher relative LC50 values for Chinook compared with coho merits further investigation, including for the potential for population‐relevant sublethal effects. Environ Toxicol Chem 2023;42:815–822. © 2023 His Majesty the King in Right of Canada and The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Reproduced with the permission of the Minister of Fisheries and Oceans Canada.